Genomic Insights into Cobweb Disease Resistance in Agaricus bisporus: A Comparative Analysis of Resistant and Susceptible Strains - Guohui Cheng; Xiaoya An; Yueting Dai; Changtian Li; Yu Li (Journal of Fungi)
Agaricus bisporus, a globally cultivated edible fungus, faces significant challenges from fungal diseases like cobweb disease caused by Cladobotryum mycophilum, which severely impacts yield. This study aimed to explore the genetic basis of disease resistance in A. bisporus by comparing the genomes of a susceptible strain (AB7) and a resistant strain (AB58). Whole-genome sequencing of AB7 was performed using PacBio Sequel SMRT technology, and comparative genomic analyses were conducted alongside AB58 and other fungal hosts of C. mycophilum. Comparative genomic analyses revealed distinct resistance features in AB58, including enriched regulatory elements, specific deletions in AB7 affecting carbohydrate-active enzymes (CAZymes), and unique cytochrome P450 (CYP) profiles. Notably, AB58 harbored more cytochrome P450 genes related to fatty acid metabolism and unique NI-siderophore synthetase genes, contributing to its enhanced environmental adaptability and disease resistance. Pan-genome analysis highlighted significant genetic diversity, with strain-specific genes enriched in pathways like aflatoxin biosynthesis and ether lipid metabolism, suggesting distinct evolutionary adaptations. These findings provide valuable insights into the genetic basis underlying disease resistance in A. bisporus, offering a foundation for future breeding strategies to improve fungal crop resilience.